What's wrong with postmodernism critical theory and the ends of philosophy - Norris, Christopher 1947- (Parallax (Baltimore, Md.), 1990)
In What's Wrong with Postmodernism Norris critiques the "postmodern-pragmatist malaise" of Baudrillard, Fish, Rorty, and Lyotard. In contrast he finds a continuing critical impulse -- an "enlightened or emancipatory interest" -- in thinkers like Derrida, de Man, Bhaskar, and Habermas. Offering a provocative reassessment of Derrida's influence on modern thinking, Norris attempts to sever the tie between deconstruction and American literary critics who, he argues, favor endless, playful, polysemic interpretation at the expense of systematic argument.